(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
The article presents the main provisions on the study of the organization of production, evaluation of the effectiveness of the processes of organizational and technical development of the enterprise. The features of the division and cooperation of labor, rationing, and increasing labor productivity are determined.